Integrated Management Of Water Resources In The Valley Of Oued-souf (algeria): Issues Fitness For A New Strategy - Khechana, S.; Derradji, F.; Derouiche, A. (University of Eloued جامعة الوادي, 2010)
This study designed to analyze and evaluate the results of trend scenarios of the strategy management of water resources used in the valley of Oued-Souf, who led the region to a truly dramatic situation and almost desperate: rise of groundwater and its adverse consequences. In terms of this work, we seek a model (plan) for the development of these resources according to criteria of sustainability, and will take into account socio-economic and ecosystem aspect. That by adaptation and implementation of integrated management of water resources (IMWR) in this unit of water resources, to meet the needs of decision support in water management, so as to guide and mobilize progressive human resources, information, financial and material, as well as various private and public sectors towards finding concrete and measurable results of water and ecosystems.
Articale in Journal of fundamental and Applied Sciences Vol. 02 N. 02
Keywords: Rise of groundwater, Oued-Souf valley, integrated management of water resources (IMWR), criteria of sustainability, ecosystems.